PENGARUH UKURAN KAP, OPINI AUDITOR, UKURAN PERUSAHAAN, TINGKAT PROFITABILITAS, DAN KOMPLEKSITAS OPERASI PERUSAHAAN TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan Property dan Real Estate yang Terdaftar di BEI Tahun 2012 – 2014) - Yudith Pius Stevan Kaunang; Amir Hasan; Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to Acquire empirical evidence of firm size, Auditor Opinion, company size, level of complexity of the operations of the Company and Profitability effect on audit delay on the company's property and real estate listed in Indonesian Stock Exchange (BEI). The population covers all property and real estate companies listed on the Indonesian Stock Exchange which publishes financial reports that show data that supports the analysis of the factors that affect audit delay. Further analysis of data using multiple regression analysis through SPSS 17.0 software msi. The results showed that company size has an influence on Audit Delay on Property and real estate company listed on the Indonesia Stock Exchange in 2012 - 2014. Public Accounting Firm size has an influence on Audit Delay on Property and real estate company listed on the Indonesia Stock Exchange , The complex does not have an influence on Audit Delay on Property and real estate company listed on the Indonesia Stock Exchange. Profitability has no effect on Audit Delay on Property and real estate company listed on the Indonesia Stock Exchange. Opinion Auditor has no effect on Audit Delay on Property and real estate company listed on the Indonesia Stock Exchange.Keywords: Firm Size, Auditor Opinion, Company Size, Profitability, Complexity of Operations, Audit Delay